Habitat Characteristics of Endemic Species of Walking Shark (Hemiscyllium Halmahera) for Proposed Protection Areas on Ternate Island, North Maluku - Galitan, Zulfikar; Wahidin, Nurhalis; Irham, Irham (Agrikan Jurnal Agribisnis Perikanan, 2023)
The walking shark (Hemiscyllium halmahera) is one of the endemic species in North Maluku and it can be found in the waters of PulauTernate. There is less Information about walking sharks, so more research is needed about this species. Moreoverthe information related to habitat conditions and priority areas for shark protection is also limited especially on the west coast of Ternate Island, so more research is also needed for this species. This study aims to describe the characteristics of habitat distribution and identify areas for priority protection for shark species (Hemiscyllium halmahera) in the sea water of Ternate island. Related to these conditions, it is required to forma proposed priority area protection scheme using Marxan software.In a Marxan analysis conservation features and cost features are needed to make a priority area scheme. The results of the Marxan analysis indicate that 20% of scenario is very priority with an area of 66.3 ha, a scenario of 30% with an area of 65.6 ha, and a scenario of 50% with an area of 71.0 ha from the total area of 421.4 ha. Scenario 20% is the most suitable location to serve as a proposed marine protected area, especially the Halmahera walking shark so that in the future it can be expected to be a priority marine protection area that can grow optimally.